FACTORS RELATED TO BODY IMAGE AND IT CORRELATION WITH NUTRITIONAL STATUS AMONG FEMALE ADOLESCENTS: A LITERATURE REVIEW - Lusiana Pradana Hariyanti; Nila Reswari Haryana (Media Gizi Indonesia, 2021)
Adolescence is the transition period from children to adults. Adolescents, especially girls, are vulnerable to nutritional problem, one of the factors is due to the perception of body image. Body image can aﬀect nutritional status if an individual has a negative body image, in which the perception that someone consciously or unconsciously cannot accept her body shape. It aﬀects the behavior of adolescent girls related to nutrition to achieve their body goal in various ways that increase risk of becoming nutritional problems (under or over nutrition). The aims of this study is ﬁnd out factors related to body image and it correlation with nutritional status in female adolescent using a literature review approach. This literature review research takes various sources of articles which published in the last 10 years (2010–2020) related to the research topics. Article were searched through the PubMed - Medline and Google Scholar databases using. Keywords ”body image”, ”nutritional status”, and ”adolescent girl”. Eighteen articles according to the topic and criteria were selected for review. Based on the results of the study, it was found that body image is related to the nutritional status of adolescent girls. This is related to the lack of nutritional knowledge of adolescent girls, which aﬀects to an unhealthy and unbalanced diet. Besides, there is also a correlation of physical activity that is not balanced with food intake and the role of the environment such as family and friends which also aﬀects knowledge, food intake, and body image of adolescent girls.